Turismo, pobreza y violencia: un análisis de correlación en los municipios del estado de Michoacán - Ramos Alvarez, Patricia (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
This project seeks to measure the degree of correlation between the tourist activity indicators and indicators of violence and on the one hand by another, measure the correlation between tourism indicators and indicators of poverty in different municipalities of the State of Michoacán. The idea that tourism development is greater when the security levels are high and that this development can boost the economic capabilities to overcome problems of poverty in an area specified is common sense. However, these relationships do not arise automatically, therefore, it is necessary to count with statistical information that will allow us to measure these correlation hypothesis. Against a background of increasing violence in the State and with relatively high levels of poverty and marginalization in many municipalities, it is important to provide empirical evidence on whether betting on tourism development represents a good option for the region, especially when there are factors of culture, architecture and traditions that tend to be highly appreciated both by domestic and international tourists.

El presente proyecto busca medir por un lado el grado de correlación entre indicadores de la actividad turística e indicadores de la violencia y por otro, medir la correlación entre indicadores de turismo e indicadores de pobreza en diferentes municipios del estado de Michoacán. La idea de que un desarrollo turístico es mayor cuando los niveles de seguridad son altos y que este desarrollo puede potenciar las capacidades económicas para superar problemas de pobreza en una zona específica es de sentido común. Sin embargo, estas relaciones no se presentan en automático, por eso, es necesario contar con información estadística que nos permitan medir estas hipótesis de correlación. Ante un panorama de creciente violencia en el estado y con niveles relativamente altos de pobreza y marginación en muchos municipios, es importante proporcionar evidencia empírica sobre si la apuesta a un desarrollo turístico representa una buena opción para la región, máxime cuando en ella se destacan factores de cultura, de arquitectura y de tradiciones que suelen ser altamente apreciados tanto por turistas nacionales como internacionales.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2016-0383; Correlación; Capacidades económicas; Desarrollo turistico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6102